Polyethylene Composites with Segregated Carbon Nanotubes Network: Low Frequency Plasmons and High Electromagnetic Interference Shielding Efficiency - Vovchenko, Ludmila (Materials (Basel), 2020)
Polyethylene (PE) based composites with segregated carbon nanotubes (CNTs) network was successfully prepared by hot compressing of a mechanical mixture of PE and CNT powders. Through comparison with a composite comprising randomly distributed carbon nanotubes of the same concentration, we prove that namely the segregated CNT network is responsible for the excellent electrical properties, i.e., 10(−1) S/m at 0.5–1% and 10 S/m at 6–12% of CNT. The investigation of the complex impedance in the frequency range 1 kHz–2 MHz shows that the sign of real part of the dielectric permittivity [Formula: see text] changes from positive to negative in electrically percolated composites indicating metal-like behavior of CNT segregated network. The obtained negative permittivity and AC conductivity behavior versus frequency for high CNT content (3–12%) are described by the Drude model. At the same time, in contrast to reflective metals, high electromagnetic shielding efficiency of fabricated PE composites in the frequency range 40–60 GHz, i.e., close to 100% at 1 mm thick sample, was due to absorption coursed by multiple reflection on every PE-CNT segregated network interface followed by electromagnetic radiation absorbed in each isolated PE granule surrounded by conductive CNT shells.